Role of receptor protein tyrosine phosphatase alpha (RPTPalpha) and tyrosine phosphorylation in the serotonergic inhibition of voltage-dependent potassium channels. - Imbrici, P; Tucker, S; D'Adamo, M; Pessia, M (2000)
The activity of voltage-gated potassium (Kv) channels can be dynamically modulated by several events, including neurotransmitter-stimulated biochemical cascades mediated by G-protein-coupled receptors. By using a heterologous expression system, we show that activating the 5-HT2C receptor inhibits both Kv1.1 and Kv1.2 channels through a tyrosine phosphorylation mechanism. The major molecular determinants of channel inhibition were identified as two tyrosine residues located in the N-terminal region of the Kv channel subunit. Furthermore, we demonstrate that receptor protein tyrosine phosphatase alpha (RPTPalpha), a receptor protein tyrosine phosphatase, co-ordinates the inhibition process mediated via 5-HT2C receptors. We therefore propose that the serotonergic regulation of human Kv1.1 and Kv1.2 channel activity by the 5-HT2C receptor involves the dual coordination of both RPTPalpha and specific tyrosine kinases coupled to this receptor.